Experience of nursing staff facing the hospitalization of burned children - Nataly Tsumura Inocencio Soares; Mauren Teresa Grubisich Mendes Tacla (Universidad de Antioquia, 2014)
Objective. To present the experiences of nursing staff working with hospitalized burned children. Methodology. Qualitative study. Data were obtained from semi-structured interviews applied to 16 people of the nursing team (12 professional technicians and 4) working at a burn treatment center. For the analysis, the Method information Interpretation of the Senses was used. The theoretical basis used to support the discussion of the study was proposed by Geertz's interpretive anthropology. Results. The narratives showed that the process of care to burned children is stressful for the participants because they are psychologically involved with the tragic story of a patient who suffered burns, and therefore with the clinical situation. This allows for the development of empathy. On the other hand there cultural involvement facing and accepting the consequences of what happened to the patient, due to the change of body image stigma that the child will suffer hamper the re-socialization of the child after discharge. Conclusion. The nursing team is affected in various ways during the care of hospitalized burned children. There is need for educational programs for their preparation in the care of these patients.